The Examining Code Choice and Speech Acts in Six Indonesian Cosmetic Taglines: A Comparative Analysis of Local Authenticity and Global Aspiration Brands - Hafsari, Rafika; Suhandono, Suhandano (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The intense competition in the Indonesian cosmetics market is a factor in analyzing the linguistic strategies used to compete in this increasingly fierce market. Besides emphasizing product quality, taglines are the primary selling point and consumer attraction. This phenomenon has created two situations. Firstly brands that initially emphasized history and local culture have shifted to adopting foreign languages ​​in their taglines. Secondly local brands that directly adopting foreign languages, not only in their brand names but also in their taglines. The methodology used in this research is a comparative discourse. That focuses on three core elements (the choice of language code, its function (indexicality), and its speech acts). This study consists of six brand taglines and 12 product taglines. All were collected from Instagram and e-commerce platforms in June 2025. The data were classified into two groups: 'Local Authenticity' (Sariayu, Mustika Ratu, Viva) and 'Global Aspiration' (Somethinc, Scarlett, Make Over). The findings of this study indicate that the 'Local Authenticity' group predominantly uses Indonesian in 55.56% of their taglines. This group is also dominant in assertive actions to index the values ​​of trust and practicality.In contrast, ‘Global Aspiration’ group favored English in 77,78% of cases, predominantly using assertive and expressive act to build an identity indexing global trends and innovation. The conclusion of this study confirms that the choice of language in a beauty product tagline is a fundamental strategic step in market segmentation and building a brand identity that aligns with target consumers in the digital age. This provides brand writers and marketers with actionable insights into strategically indexing language codes to align brand identity with target market expectations.